Malaysians' willingness to support Japanese expatriates - Ng, Siew Imm; Ang, Shiao Chin; Tee, Keng Kok (Universiti Putra Malaysia Press, 2015)
Expatriates' success studies have always focused on the expatriates' home country preparation, cross cultural adjustment ability and host country environment. This study examined the host country nationals' perspective, particularly their willingness to support Japanese expatriates. Malaysians' openness to change, openness to linguistic diversity and perceived reciprocity were found to significantly explain their willingness to support Japanese expatriates. The outcome of this study provided information to companies on strategies they can use in improving host country nationals' willingness to support expatriates.